2015
DOI: 10.1068/d13150p
|View full text |Cite
|
Sign up to set email alerts
|

From Toxic Wreck to Crunchy Chic: Environmental Gentrification through the Body

Abstract: This paper takes up the challenge o f extending and enhancing the literature on environm ental gentrification by considering bodies and embodied practices as significant dimensions o f this process. In considering the question o f how a polluted past can be mobilized as an asset for neighbourhood rebranding and gentrification, this research suggests that the conflation o f both pollution and 'health' with different kinds o f urban bodies and practices is an im portant strategy for solidifying a clean and green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 62 publications
1
66
0
4
Order By: Relevance
“…We question why and how two of the most progressive cities (when it comes to past drug and sex-work policies) develop policies to make RLDs less visible and displace sex-workers and how these policies are legitimised. Certain bodies and embodied practices like sex work apparently cannot (or not easily) be mobilised as an asset for gentrification and are considered 'dirty' or not 'fit' (see also Kern 2015). Along the same lines, Hubbard (2016) shows how retail gentrification is a form of moral regulation because it promotes particular modes of consumption over others.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We question why and how two of the most progressive cities (when it comes to past drug and sex-work policies) develop policies to make RLDs less visible and displace sex-workers and how these policies are legitimised. Certain bodies and embodied practices like sex work apparently cannot (or not easily) be mobilised as an asset for gentrification and are considered 'dirty' or not 'fit' (see also Kern 2015). Along the same lines, Hubbard (2016) shows how retail gentrification is a form of moral regulation because it promotes particular modes of consumption over others.…”
Section: Introductionmentioning
confidence: 96%
“…If we look more in detail at who, exactly, is targeted under urban regeneration in RLDs it becomes clear that illegal immigrants and drug-addicted sex-workers are the categories that has been displaced from most visible RLDs all over Europe (Kern 2015;Künkel 2012). And that the process of gentrification also coincides with greater criminalisation of migrant sex-workers in general (Andrijasevic 2004;Chimienti and Bugnion 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident here that the recognition of sex premises as potentially legal land use relies on the use of certain vocabularies and procedures which produce particular 'facts' about commercial sex in the city: despite their obvious moral dimensions, these truths are ostensibly stripped of political resonance or moral sentiment given they appear to relate solely to environmental impact and the material consequences of sexual uses of space (Frisch, 2002;Kern, 2015). In this sense, while municipal law appears unconcerned with anatomo-politics and sex itself, the suggestion here is that it is fundamentally implicated in the making of social norms through regulation of what sexual behaviour is permitted where (Hubbard, 2015).…”
Section: Sex Premises As Legal Land Usementioning
confidence: 99%
“…Recently, some researchers have observed that urban greening can trigger 'environmental-gentrification', further entrenching environmental inequalities (Checker 2011, Eckerd 2011, Kern 2015, Pearsall 2010). Environmental-gentrification occurs when the conversion of brownfields to greenspace, provision of new greenspace, or redevelopment of existing greenspace drives-up property values, because a location becomes more attractive to investors and/or more desirable for residents (Millington 2015, Quastel 2009).…”
Section: Introductionmentioning
confidence: 99%